Benzothiazole derivatives-based supramolecular assemblies as efficient corrosion inhibitors for copper in artificial seawater: Formation, interfacial release and protective mechanisms. (March 2023) - Liu, Zining; Fan, Baomin; Zhao, Jingmao; Yang, Biao; Zheng, Xingwen
Abstract: Host-guest assemblies for β-cyclodextrin (β-CD) loaded with 2-mercaptobenzothiazole (MBT) or 2-aminobenzothiazole (ABT) were constructed to distinguish their anticorrosive mechanisms for copper in aqueous phase. Their protective efficacies were assessed by weight-loss, electrochemical, surface and solution analyses for copper in the artificial seawater. Achievements proposed that MBT and ABT were stably incorporated in β-CD with distinct thermodynamic traits, which earned the optimal inhibition efficiencies of 95.6 % and 89.2 % at 0.5 g/L dosage following cathodic-dominated mixed-type inhibition mechanism. Coupling theoretical simulations, varied guest release mechanisms and different bonding strengths of Cu-S and Cu-N accounted for the differentiated inhibition behaviors. Graphical Abstract: ga1 Highlights: Distinct end groups caused varied thermodynamics for MBT or ABT assembling. Guest release achieved the protective ability of assemblies for copper in ASW. Guest state and binding atom with copper decided the driving force for release. Instability and premature ABT release lowered the inhibition effect of CD-A. Electrostatic force and chemical bonding endowed high protection power of CD-M.